About Agents and Predictive Controlles - Lima, Marcelo Lopes de; Hübner, Jomi Fred; Camponogara, Eduardo (Anais do Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações (WESAAC), 2011)
In this work we analyze the relation between intelligent BDI agents and Model Predictive Controllers (MPC). While BDI agents is a new approach to develop autonomous systems, the MPC are the most successful multivariable controllers used nowadays in the industry. The two fields can contribute to each other towards a kind of MPC agents, and we expect significant improvements in the theory and practice of actual controllers.